Applications of management science in productivity, finance, and operations - Lawrence, Kennedy D.; Klimberg, Ronald K. (Bingley, U.K. : Emerald, 2006)
Volume 12 of the'Applications of Management Science' series is directed toward the applications of management science to: Multi-Criteria Decision Making, Operations and Supply Chain Management, Productivity Management (DEA), and Financial Management. This volume will prove valuable to researchers, practitioners and students of management science and operations research. It provides an overview of some of the most essential aspects of the discipline and is an excellent point of reference for persons interested in management or management science. It focuses on four key applications of management science, and is targeted towards a wide audience of researchers, practitioners, and students.
Measuring organizational efficiency with data envelopment analysis : the Horace Mann insurance company / Peter M. Ellis -- Consumer-packaged freight delivery evaluation : a multiple criteria data envelopment analysis approach / Gary R. Reeves, Kenneth D. Lawrence, Sheila M. Lawrence -- Evaluating the operational efficiency of railway systems with sensitivity analyses to sampling variations / N.K. Kwak, Yong Soo Chun, Seongho Kim -- Input-output variable evaluation for studying DEA efficiency performance in electric utilities / David E. Schultz, Suresh K. Tadisina -- A survey of multi-objective scheduling techniques applied to the job shop problem (JSP) / David L. Bakuli -- A multi-objective mathematical programming model for audit samples of balances for accounts receivable / Kenneth D. Lawrence, Ronald Klimberg, Sheila M. Lawrence -- A multi-criteria fixed charge problem : location of service centers / Kenneth D. Lawrence, Sheila M. Lawrence, Ronald Klimberg, Jerry Fjermestad -- Identifying compounds for pharmaceutical companies' development tracks using a multi-criteria decision model / Karen M. Hogan, Gerard T. Olson, George P. Sillup -- Calculating disassembly yields in a multi-criteria decision-making environment for a disassembly-to-order system / Prasit Imtanavanich, Surendra M. Gupta -- Selection criteria for a network design model with uncertain demand / Steven Cosares, Fred J. Rispoli -- A novel approach to the continuous flow truckload routing problem / Virginia M. Miori -- Vertical cooperative advertising in a manufacturer-retailer supply channel / Susan X. Li, Zhimin Huang, Allan Ashley -- Deterministic hybrid and stochastic combinatorial optimization treatments of an electronic product disassembly line / Seamus M. McGovern, Surendra M. Gupta -- Using'mirror worlds' to support supply network management / Daniel O'Leary -- An analytic network process model for internal auditor selection / Joseph Sarkis, Inshik Seol -- A two-dimensional minimal-repair warranty policy / Amitava Mitra, Jayprakash G. Patankar -- A cost variance investigation using belief functions / Thomas W. Lin, Daniel E. O'Leary, Hai Lu -- Chance-constrained programming with skewed distributions of matrix coefficients and applications to environmental regulatory activities / William W. Cooper, Vedran Lelas, David W. Sullivan -- Optimal advertising pulsation policy for a continuous model of advertising competition / Hani I. Mesak, Hongkai Zhang.
Keywords: Management science